ANALYZING THE IMPACT OF SOME FISCAL AND MONETARY POLICIES IN THE VALUE OF AGRICULTURAL OUTPUT IN SELECTED ARAB COUNTRIES FOR THE PERIOD (1990-2010) COMPARATIVE STUDY - Ahmed Al-Mshhdani (Mesopotamia Journal of Agriculture)
The research aims to identify some of the effects of fiscal and monetary policies in the value of agricultural output in selected Arab countries during the period (1990-2010). It has become necessary to know the role of fiscal and monetary policies tools applied during the study period, and its objectives towards the agricultural sector in the countries of the research sample. So the research presumer to know a number of factors affecting the value of agricultural output, to present these factors are: (inflation , the size of agricultural loans, surplus or budget deficit, the exchange rate), was the search explore know the effect of these factors on the value of agricultural output in Iraq and Egypt during the period (1990-2010) and the comparison between the two, so the search method depends on two main aspects: first, the descriptive side which was based on previous studies , who studied the same subject, and secondly, the quantitative aspect, which is based on the multiple linear regression model, and then interpret the results of the quantitative aspect to assess the practical side of the study. It also included research on the most important conclusions was including: the impact of fiscal and monetary policies in Iraq were limited due to economic conditions experienced by Iraq in the nineties and after the year (2003 ), which were not clear and dramatically reverse of what it was in Egypt, Accordingly, the research recommends: the use of fiscal and monetary policies more clearly by lawmakers and the need for state intervention in the formulation of these policies in an integrated manner to improve the performance of the economy and accelerate development and which are reflected directly in upgrading the performance of sectors , including the agricultural sector.